2004
DOI: 10.1002/macp.200300099
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a New Macromonomer from 2‐(Dimethylamino)ethyl Methacrylate Bearing 1‐(Isopropenylphenyl)‐1,1‐dimethylmethyl Isocyanate Group

Abstract: Summary: The telomerization of 2‐(dimethylamino)ethyl methacrylate (DMAEMA) with 2‐mercaptoethanol in acetonitrile shows that the telogen can react with the monomer by nucleophilic addition. It is to say that the tertiary amino group leads to nucleophilic addition rather than telomerization. The oligomers thus obtained were functionalized with 1‐(isopropenylphenyl)‐1,1‐dimethylmethyl isocyanate (TMI) in anhydrous toluene to afford macromonomers. These macromonomers were copolymerized with styrene and the r1, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…The acrylate group has a higher reactivity than methacrylate as shown elsewhere. 88 However, the rates are dependent on the nature of solvent, i.e., in polar solvents the reaction can take 3-4 h, while in apolar solvents much longer reaction times are required. 82,83 Recently, Lowe and coworkers showed that this reaction can be catalyzed by dimethyl phenyl phosphine, reducing the reaction time to a few minutes.…”
Section: Synthesis Of Macromonomers Using 16-hexanediol Diacrylate Amentioning
confidence: 99%
“…The acrylate group has a higher reactivity than methacrylate as shown elsewhere. 88 However, the rates are dependent on the nature of solvent, i.e., in polar solvents the reaction can take 3-4 h, while in apolar solvents much longer reaction times are required. 82,83 Recently, Lowe and coworkers showed that this reaction can be catalyzed by dimethyl phenyl phosphine, reducing the reaction time to a few minutes.…”
Section: Synthesis Of Macromonomers Using 16-hexanediol Diacrylate Amentioning
confidence: 99%
“…Two commercially available monomers are often used: 3‐isopropenyl‐α,α′‐dimethylbenzyl isocyanate (TMI)129 or 2‐isocyanatoethyl (meth)acrylate (IEM130 or IEA131). TMI, is reluctant to homopolymerize,132 and so its use is restricted to copolymerizations, while IEM or IEA can be both copolymerized and homopolymerized. These isocyanate monomers have both been previously used in anionic polymerization and free radical (co)polymerizations,133, 134 and more recently, in RAFT polymerization yielding functional polymers 131, 135…”
Section: Raft Polymerizationmentioning
confidence: 99%
“…The nature of the telogen agent exhibited no influence on the distribution of polymers since in both cases a polydispersity index (PDI) around 2.0 was determined by SEC technique. These SEC values were appropriate for such telogen agents, monomer, and degree of polymerization ( n < 100), as reported previously …”
Section: Resultsmentioning
confidence: 86%